Get fit with Apple watch : using the Apple watch for health and fitness - Taylor, Allen G. (Apress, 2015)
Get Fit with Apple Watch is the concise introduction to the amazing new Apple Watch. It's the first book specifically focused on the Apple Watch's most important function: health and fitness. The book gives readers just what they need to know to understand all functionality of the Apple Watch and to set up their Apple Watch. Get Fit with Apple Watch clearly explains the Apple Watch's fitness and health-tracking functions, showing readers different ways to integrate these functions into their daily lives and regular workout routines. Veteran technology author Allen Taylor is also a participant in the Apple Watch Research Kit study in cardiovascular fitness conducted by Stanford University, and adds a chapter devoted to the Apple Watch Research Kit, explaining the benefits of the associated medical research apps and how users can participate in these world-changing programs. Perfect for the gadget-loving athlete and fitness fan! You'll learn: How the Apple Wat ch subtly encourages healthy habits How the Apple Watch helps build cardiovascular fitness and endurance How to multiply the value of the Apple Watch by pairing it with your iPhone How third party fitness apps multiply the capabilities of the Apple Watch How to participate in the Apple Watch Research Kit program Brief explanations of the leading third-party app available for the Apple Watch (including more than just fitness and health apps.